Analisis Bauran Pemasaran (4P) pada Agrowisata Jeruk Siam Eptilu di Kabupaten Garut - Zein, Nufika Shilhan; Djuwendah, Endah; Saidah, Zumi (Universitas Galuh, 2026)
Agrotourism plays a strategic role in supporting rural economic development, enhancing community welfare, and promoting sustainable tourism practices. As one of the leading agrotourism destinations in Garut Regency, Eptilu Siam Orange Agrotourism offers unique attractions such as orange-picking activities, educational tours, and traditional culinary experiences. However, the effectiveness of its marketing strategy is essential to increase competitiveness and attract wider visitor segments. The purpose of this study is to analyze the application of the marketing mix (4P)—product, price, place, and promotion at Eptilu Siam Orange Agrotourism based on visitor perceptions. The research employed a quantitative descriptive approach using a Likert-scale questionnaire distributed to 100 visitors. The data were analyzed descriptively to evaluate the performance of each 4P component. The results show that all aspects of the marketing mix are rated within the “good” to “very good” categories, with the highest scores found in the product and price components. Visitors highly appreciate the orange-picking experience, educational activities, and culinary services provided. Meanwhile, the promotion component particularly digital promotion requires further improvement to reach broader market segments. These findings highlight the importance of strengthening marketing strategies to support sustainable agrotourism development in Garut Regency.